AN UPDATE ON BURNING MOUTH SYNDROME (A SELECTIVE REVIEW OF THE LITERATURE) - Febrina Rahmayanti (Faculty of Dentistry, Universitas Indonesia, 2006)
Burning mouth syndrome (BMS) is one of the orofacial pain problems. BMS has been fefined as burning pain in the tongue or oral mucous membranes, usually without accompanying clinical and laboratory findings. BMS affecting mostly women, is a constant and aggravating source of discomfort for more than 1 million adults in the world. This paper provides updated information on burning mouth syndrome and current etiopathogenesis and treatment options are discussed.